The Geographical Distribution of Global Biobanks - Farzad Parvizpour; Sarvenaz Salahi; Mohammad Amin Mahmanzar; Karim Rahimian; Neda Esfandiari; Zahra Fatahi; Niousha Khoshdast; Reyhaneh Yarmohammadi; Mohamad Amir Amirkhani; Arefeh Jafarian (Cell Journal)
This study aimed to comprehensively review the global biobanks to visualize their geographical distribution. The protocolfor this review consisted of the following steps: i. Developing a search strategy to identify biobanks from each continent,ii. Defining variables (such as tissue-based, cell-based, and gene-based biobanks) and organizing them in Excel sheetsfor data collection, iii. Collecting data, iv. Removing duplicate and invalid entries, v. Structuring the database, and vi.Analyzing the data. MATLAB software was utilized for data analysis and chart plotting. Data on global biobanks aimedto collected through targeted searches of databases, publications, and registries using predefined variables such asbiobank type, location, and accessibility. The data were organized, cleaned to remove duplicates, and analyzed usingMATLAB to visualize geographical distribution and prevalence patterns. Tissue and cell-based, tissue-based, and cellbasedbiobanks were the most common type of global biobanks with a prevalence of 30.4, 27.93, and 25.15%. UnitedKingdom (n=78, P=43.09%), Canada (n=43, P=23.75%), and the United States (n=33, P=18.23%) were the countrieswith a higher frequency of tissue-based biobanks (domain frequency: 1-78; 0.55-43.09%). However, tissue and genebasedbiobanks had the most minor frequency and were only in two countries of Spain (n=1, P=25%) and the UnitedKingdom (n=3, P=75%). The results of this study indicate that the feasibility of designing and conducting biobanksvaries by type. Tissue and cell-based biobanks were found to be more prevalent, followed by tissue-based, cell-based,cell and gene-based, tissue, cell, and gene-based, gene-based, and finally, tissue and gene-based biobanks. Thisstudy represents the initial step in creating a global database by identifying all types of biobanks worldwide.